Ulu al-Albab in the Qur'an: Meaning, Characteristics, and Role in Social Change - Zaini, Muhammad (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
This study aims to examine the Qur'anic verses that mention "ulū al-albāb." Using a qualitative research design and content analysis, the primary data were sourced from the Qur'an, while secondary data were collected from tafsir texts and scholarly articles. The findings reveal that "ulū al-albāb" possess profound intellectual and spiritual insight, characterized by knowledge, adherence to divine covenants, maintaining family ties, fear of God, patience, prayer, altruism, and repelling evil with good. These attributes distinguish them from ordinary intelligent individuals. "Ulū al-albāb" are well-suited to lead and implement "dakwah" (Islamic propagation), especially in methods requiring deep understanding and strategic implementation. They are expected to serve as agents of social change by occupying significant positions in societal institutions, leveraging their influence to drive positive transformations. This study highlights the importance of integrating textual and contextual approaches in understanding "dakwah" and the critical role of "ulū al-albāb" in Islamic thought and social change.